The Utilization of E-Commerce to Improve Access to Nutrition in Stunting Prevention in Lebak Regency: An Innovative Prototype Study - Sudiantini, Dian; Manrejo, Sumarno; Narpati, Bintang (CV. Era Digital Nusantara, 2025)
Stunting, a major public health concern in Indonesia, particularly in rural areas such as Lebak Regency, stems from persistent nutritional deficiencies and limited access to affordable, high-quality food. This study examines the potential of e-commerce as an innovative solution to enhance access to nutrition and contribute to stunting prevention. An e-commerce prototype was developed to connect local food producers with underserved consumers, ensuring the availability of diverse and affordable nutritional products. Using a mixed-methods approach, the study assessed the platform's feasibility, usability, and impact on nutritional access and community welfare.Quantitative data revealed a significant improvement in dietary diversity and affordability among targeted households, while qualitative insights highlighted increased awareness of nutrition and economic benefits for local producers. The platform also addressed logistical barriers by optimizing distribution networks in geographically isolated areas. Moreover, the initiative empowered small-scale enterprises, enhancing their market reach and income sustainability.The findings demonstrate the scalability and sustainability of e-commerce as a tool for addressing nutritional challenges in rural settings. This study provides actionable insights for policymakers, healthcare providers, and digital innovators, advocating for the integration of e-commerce into national strategies for stunting prevention and public health improvement. Future research should explore broader applications of digital platforms in addressing complex health challenges.